ROSIHAN ANWAR SEBAGAI SEJARAWAN - Husni, Muhammad (Paradigma: Jurnal Kajian Budaya, 2024)
This study explores the life of Rosihan Anwar, a famous Indonesian historian and journalist. He can be considered a historian because he applied historical methods in several of his works. As a historian, he had an exceptional ability to collect oral sources by means of interviews with the actors in or eyewitnesses to the event. Despite limitations in terms of the use of written sources because journalists had a tight deadline for publishing their articles, Rosihan was able to produce historical writings with strong rhetoric and to present information in an interesting way, making them easily understood by a wide audience. As a history recorder during the Indonesian Independence Revolution era, he produced many works which contributed to Indonesian historiography, which were written using an alternative historical writing approach known as “small history”.